Aplicación de estrategias metodológicas basadas en el juego que aporta al desarrollo cognitivo, socio-afectivo y motriz en niños y niñas de 4 a 5 Años en el centro de desarrollo infantil teniente Hugo Ortíz período lectivo 2010-2011 - Barcia Sánchez, Maribel Herlinda (2011)
This project aims and improves teaching learning process where the development a tutorial is the primary objective for give teacher’s alternatives to kindergartens and these in turn improve their learning process. Where the proper handling of the game through strategies given help to develop processes of class innovative and creative succeed in strengthening their coming to the aforementioned methodology to education significant. Jean Piaget in his studies he notes that it is above all essential to note that the game is not their child to do "naturally", not a natural ability, but an innate ability. As Thus, to develop the necessary capacity another that gives meaning to certain actions the child small place spontaneously…